Global impact of particulate matter on ischemic stroke - Xie, Zhouyu; Shu, Peng; Li, Fei; Chen, Yi; Yu, Wangfang; Hu, Ronglei (Frontiers in Public Health, 2024)
Objective: This studyassesses the worldwide impact of ischemic stroke caused by ambient particulate matter pollution between 1990 and 2019, utilizing data from the Global Burden of Disease (GBD) 2019. Methods:An analysis was conducted across various subgroups, including region, Socio-demographic Index (SDI) level, country, age, and gender. The study primarily examined metrics such as death cases, death rate, Disability-Adjusted Life Years (DALYs), DALY rate, and age-standardized indicators. The Estimated Annual Percentage Change (EAPC) was calculated to assess trends over time. Results: The study found a moderate increase in the global burden of ischemic stroke attributed to ambient particulate matter, with the age-standardized DALY rate showing an EAPC of 0.41. Subgroup analyses indicated the most substantial increases in Western Sub-Saharan Africa (EAPC 2.64), East Asia (EAPC 2.77), and Eastern Sub-Saharan Africa (EAPC 3.80). Low and middle SDI countries displayed the most notable upward trends, with EAPC values of 3.36 and 3.58 for age-standardized death rate (ASDR) and DALY rate, respectively. Specifically, countries like Equatorial Guinea, Timor-Leste, and Yemen experienced the largest increases in ASDR and age-standardized DALY rate. Furthermore, both death and DALY rates from ischemic stroke due to particulate matter showed significant increases with age across all regions. Conclusions: The study highlights the increasing worldwide health consequences of ischemic stroke linked to particulate matter pollution, particularly in Asia and Africa. This emphasizes the critical necessity for tailored public health interventions in these regions.